2014
DOI: 10.1097/ccm.0b013e3182a27759
|View full text |Cite
|
Sign up to set email alerts
|

Consulting Communities When Patients Cannot Consent

Abstract: Objective To assess the range of responses to community consultation efforts conducted within a large network and the impact of different consultation methods on acceptance of exception from informed consent (EFIC) research and understanding of the proposed study. Design A cognitively pre-tested survey instrument was administered to 2,612 community consultation participants at 12 US centers participating in a multi-center trial of treatment for acute traumatic brain injury (TBI). Setting Survey nested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A study that used surveys to assess the acceptability of exception from informed consent for research in emergency settings found that interactive community consultations resulted in significantly higher acceptability and higher level recall of study content than non-interactive consultations [43]. Approaches to evaluating community engagement activities were briefly described in the H3Africa guidelines including use of theory-based methodology, monitoring participation at events and meetings, documentation to track discussions, and use of interviews, focus groups and surveys [39].…”
Section: Discussionmentioning
confidence: 99%
“…A study that used surveys to assess the acceptability of exception from informed consent for research in emergency settings found that interactive community consultations resulted in significantly higher acceptability and higher level recall of study content than non-interactive consultations [43]. Approaches to evaluating community engagement activities were briefly described in the H3Africa guidelines including use of theory-based methodology, monitoring participation at events and meetings, documentation to track discussions, and use of interviews, focus groups and surveys [39].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of lower EFIC acceptance among black respondents are important and have been suggested elsewhere, though these differences were not observed in the larger ProTECT community consultation study (6, 19). Whether the high rate of acceptance among Hispanic subjects would persist in larger samples is unknown.…”
Section: Discussionmentioning
confidence: 52%
“…EFIC acceptance exceeded acceptance observed in a large study of community consultation participants across 12 ProTECT III sites. In that study, 71% and 54% were accepting of personal and general EFIC enrollment respectively, compared to 78% and 72% here (19). Similar patterns were found in RAMPART-related studies conducted within the same network (6, 13, 23).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations